ANALISIS EFISIENSI PRODUKSI KOMODITAS KAPAS DI SULAWESI SELATAN - SYAM, AMIRUDDIN (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 5, No. 3 November 2005)
The end target of development policy on plantation is to increase its product export rate as well as to supply sufficiently its domestic industry needs. It could be achieved by increasing its productivity and enhancing its production efficiency. The objective of this research is to study cotton-farming performance in order to collect its input-output data, the function of the cotton production data including its production possibility frontier, and too see which variable might influence the production function. The result shows that the TE (Technical Efficiency) average for sampled cotton farmers is 0.70 in normal distribution. The application of the new technology on the transgenic molecular cotton and cooperation with operating company are likely able to give the farmers prospective alternative in the future as it gives a greater benefit than that one they earned previously by planting local variety cotton. This reason is supported by sensitivity analyses in which if the cottonseeds price is reduced then the farmers are still benefited. The transgenic cottonseed has better germination rate and viability as well as higher quality and quality of its harvested production. These results could be achieved only if all the physical agronomic requirements such as favorable agro-climate during vegetative stage are met adequately in addition to proper recommended fertilizing.
Keywords: Efficiency, Production, Cotton